Factors of Homicide in the Punjab: Evidence from Convicted Prisoners (Journal of Politics and International Studies, 2021)
The main purpose of the present research was to analyze socio-economic and politico-legal factors of execution of murder in Punjab, Pakistan. In the recent era, multiple factors are contributing and motivating individuals to commit murder and face court proceedings. For the current study, a survey method was conducted to collect information from the convicted prisoners. A proportionate random sampling technique was employed to draw a sample for eight jails of the Punjab province. A sample size of 367 prisoners was drawn from the target population. Pretesting was done and the value of Cronbach’s Alpha was ranging from .70 to .90. Furthermore, Structural Equation Modeling (SEM) was employed to test the hypotheses. The study findings showed that there is a significant impact of socio-economic and politico-legal factors on the execution of the murder. Moreover, the results supported the argument that family, property and land disputes, revenge and enmity, involvement in the robbery, and social interaction with criminals had a significant impact on the execution of the murder. Furthermore, Statistical Package for Social Sciences (SPSS), Amos, and Statistica were used to analyze data and to draw conclusions.